Clinical Risk Scoring Models for Prediction of Acute Kidney Injury after Living Donor Liver Transplantation: A Retrospective Observational Study. - Mi Hye Park; Haeng Seon Shim; Won Ho Kim; Hyo-Jin Kim; Dong Joon Kim; Seong-Ho Lee; Chung Su Kim; Mi Sook Gwak; Gaab Soo Kim (PLoS ONE, 2015)
Acute kidney injury (AKI) is a frequent complication of liver transplantation and is associated with increased mortality. We identified the incidence and modifiable risk factors for AKI after living-donor liver transplantation (LDLT) and constructed risk scoring models for AKI prediction. We retrospectively reviewed 538 cases of LDLT. Multivariate logistic regression analysis was used to evaluate risk factors for the prediction of AKI as defined by the RIFLE criteria (RIFLE = risk, injury, failure, loss, end stage). Three risk scoring models were developed in the retrospective cohort by including all variables that were significant in univariate analysis, or variables that were significant in multivariate analysis by backward or forward stepwise variable selection. The risk models were validated by way of cross-validation. The incidence of AKI was 27.3% (147/538) and 6.3% (34/538) required postoperative renal replacement therapy. Independent risk factors for AKI by multivariate analysis of forward stepwise variable selection included: body-mass index >27.5 kg/m2 [odds ratio (OR) 2.46, 95% confidence interval (CI) 1.32-4.55], serum albumin <3.5 mg/dl (OR 1.76, 95%CI 1.05-2.94), MELD (model for end-stage liver disease) score >20 (OR 2.01, 95%CI 1.17-3.44), operation time >600 min (OR 1.81, 95%CI 1.07-3.06), warm ischemic time >40 min (OR 2.61, 95%CI 1.55-4.38), postreperfusion syndrome (OR 2.96, 95%CI 1.55-4.38), mean blood glucose during the day of surgery >150 mg/dl (OR 1.66, 95%CI 1.01-2.70), cryoprecipitate > 6 units (OR 4.96, 95%CI 2.84-8.64), blood loss/body weight >60 ml/kg (OR 4.05, 95%CI 2.28-7.21), and calcineurin inhibitor use without combined mycophenolate mofetil (OR 1.87, 95%CI 1.14-3.06). Our risk models performed better than did a previously reported score by Utsumi et al. in our study cohort. Doses of calcineurin inhibitor should be reduced by combined use of mycophenolate mofetil to decrease postoperative AKI. Prospective randomized trials are required to address whether artificial modification of hypoalbuminemia, hyperglycemia and postreperfusion syndrome would decrease postoperative AKI in LDLT.